A Brief Study on Land Degradation and Urban Expansion in Nagarjun Municipality, Kathmandu, Nepal - Yadav, Yogendra Kumar (The Himalayan Geographers, 2025)
Land degradation poses a serious global challenge with around 25% of world's land mass degraded badly affecting over 1.5 billion people worldwide. Urbanization plays fairly a significant role among major contributors as expanding cities tend to rapidly convert agricultural land into sprawling built-up areas. This study utilizes MEDALUS framework assessing land degradation vulnerability in Nagarjun Municipality situated within Kathmandu Valley of Nepal somewhat effectively. Four composite indices were calculated including Soil Quality Index by 1.318 and Vegetation Quality Index standing at 1.261. Values were combined rather haphazardly deriving an Environmental Sensitivity Area Index score of 1.566 pretty precisely it seems. This value puts area directly in critical degradation category exceeding severe vulnerability threshold of 1.37 pretty significantly in our time. Major contributing factors include steep slopes and shallow erosion-prone soils alongside unhappily insufficient vegetation coverage with merely 44% of land protected. Nagarjun has rapidly emerged as a swiftly rising suburban region within Kathmandu Valley at the same time. By 2018 it had backed 3477 businesses employing 11001 people and saw a rather quick spike in demand for housing. Rapid urban expansion alters land use pretty drastically and puts tremendous pressure on infrastructure heightening erosion risks significantly everywhere. High-risk zones should be prioritized for reforestation efforts and rigorous erosion control measures while land-use planning gets guided by robust data.